Pressure‐Tuned Structure and Property of Optically Active Nanocrystals. Issue 10 (11th January 2016) - Bai, Feng; Li, Binsong; Bian, Kaifu; Haddad, Raid; Wu, Huimeng; Wang, Zhongwu; Fan, Hongyou
Abstract : Investigations through high‐pressure X‐ray scattering and spectroscopy in combination with theoretical computations shows that high‐pressure compression can systematically tune the optical properties and mechanical stability of the molecular nanocrystals.